2022
DOI: 10.1126/scitranslmed.abo2652
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer nanotherapy for severe COVID-19 attenuates inflammation and neurological injury markers and improves outcomes in a phase2a clinical trial

Abstract: Hyperinflammation triggered by SARS-CoV-2 is a major cause of disease severity, with activated macrophages implicated in this response. OP-101, a hydroxyl-polyamidoamine dendrimer– N -acetylcysteine conjugate that specifically targets activated macrophages, improves outcomes in preclinical models of systemic inflammation and neuroinflammation. In this multicenter, randomized, double-blind, placebo-controlled, adaptive phase 2a trial, we evaluated safety and preliminary efficacy of OP-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Conjugation of small molecule drugs to dendrimer nanoparticles have been posited as a mechanism to improve PK properties. In fact, hydroxyl PAMAM dendrimer conjugates discovered by our team are currently being tested in phase I (NCT05395624 and NCT03500627) and phase II clinical trials (NCT04458298), with positive Phase 2a results in severe COVID-19 patients in several measures of efficacy including survival, attenuation of neurological injury, and hyper-inflammation [ 53 ]. Several preclinical studies have demonstrated that dendrimer conjugation of small molecules can prolong their half-life in target tissues [ 44 , 45 , 46 , 47 ] and deliver drugs in a targeted manner to areas of neuroinflammation where they are engulfed by activated microglia [ 44 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugation of small molecule drugs to dendrimer nanoparticles have been posited as a mechanism to improve PK properties. In fact, hydroxyl PAMAM dendrimer conjugates discovered by our team are currently being tested in phase I (NCT05395624 and NCT03500627) and phase II clinical trials (NCT04458298), with positive Phase 2a results in severe COVID-19 patients in several measures of efficacy including survival, attenuation of neurological injury, and hyper-inflammation [ 53 ]. Several preclinical studies have demonstrated that dendrimer conjugation of small molecules can prolong their half-life in target tissues [ 44 , 45 , 46 , 47 ] and deliver drugs in a targeted manner to areas of neuroinflammation where they are engulfed by activated microglia [ 44 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by our lab has shown that these dendrimers selectively localize in activated glia in the brain in small and large animal models, and can deliver drugs to the site of injury, thus producing positive therapeutic outcomes [ 33 , 48 , 50 , 51 , 52 ]. In fact, hydroxyl-dendrimer nanotherapy was recently shown to attenuate inflammation and neurological injury markers and improve outcomes in a phase 2a clinical trial in patients with severe COVID-19 [ 53 ]. We therefore aimed to improve the oral bioavailability, half-life, and brain delivery of DPTIP by conjugating it to a hydroxyl-PAMAM dendrimer delivery system (D-DPTIP).…”
Section: Introductionmentioning
confidence: 99%
“…In a phase 2a therapeutic trial, patients with severe COVID-19 received OP-101, a hydroxyl-polyamidoamine dendrimer-N-acetyl cysteine combination that targets active macrophages. Op-101 was well tolerated and reduced the probability of death or mechanical ventilation at 30 and 60 days following treatment compared to a control group [16]. Treatment with OP-101 resulted in a decrease in serum levels of proinflammatory and neurological indicators (neurofilament light chain and glial fibrillary acidic protein).…”
Section: Introductionmentioning
confidence: 91%
“…OP-101 reduced morbidity and mortality in hospitalized patients with severe COVID-19. Indeed, at day 60, only three of seven patients given placebo were surviving, whereas they were 14 of 17 for OP-101–treated patients [ 51 ].…”
Section: Clinical Trials With Pamam Dendrimersmentioning
confidence: 99%